Study of nitrate accumulation in herbs of Thymus pulegioides L. for flora of Ukraine - Ya. M. Steshenko; O. V. Mazulin (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2020)
Thymus pulegioides L. syn. (Thymus ovatus Mill.) of family, Lamiaceae is a fairly common species in Ukraine. Given the literature data, the studied species needs a more thorough study of nitrate accumulation due to the ecological situation in Ukraine, as well as the search for herbal medicinal products with sufficient raw material base and a minimum amount of carcinogenic and harmful substances.